The Effect of Country of Origin and Innovation on Repurchase Intention with Perceived Quality as Mediation in the European Product-Based Marine Engine Industry - Muslim, Abdul; Permana, Dudi (Dinasti International Journal of Management Science, 2024)
The shipping industry in Indonesia has developed into one of the important parts of the country's economy. As a maritime country with thousands of islands and vast search, Indonesia has a growing need for a fleet of ships. One of the key aspects in the construction of marine vessels is the use of reliable and high-quality ship engines. The current trade balance business in Indonesia, the majority of which uses sea vessel transport, reflects the trend of the shipping business in terms of Export Import in Indonesia over the past few years experiencing a surplus. Therefore, this study aims to measure the variables of innovation, country of origin (COO), repurchase intention and perceived quality in the marine engine industry based on European products. This research will make a theoretical contribution by providing and developing a deeper understanding of the variables that impact Repurchase Intention in the context of the European product-based marine engine industry. Expectancy Disconfirmation Theory is a theory used to distinguish between individual expectations and actual experiences affecting perceptions of a product or service. According to this theory, when individuals feel that their experience exceeds their expectations, they will feel satisfied. However, if the experience is not as expected, then there tends to be a feeling of dissatisfaction. The data processed were 150 samples and were taken from 3 major cities of marine engine manufacturing in Indonesia, namely Jakarta, Batam and Surabaya, using nonprobability sampling with purposive sampling technique and processed using Structural Equation Model (SEM) based on Partial Least Square (PLS) through SmartPLS 3 application.